تعليمية النص الإنشائي في الدرس اللّغوي الحديث - أوستن أنموذجا - - زريق, إبتسام (حوليات المخبر; No 02 (2014): مجلة حوليات المخبر)
يعاني طالب اللغة العربية من مشاكل أثناء تلقيه النصوص اللغوية والأدبية على حد سواء؛ فهذه المشاكل تظهر عجزه عن التأدية الفعلية للغة. فإذا أتقن نصوص صورها الصوتية. الصرفية. النحوية. الدلالية والبلاغية فإنه لا يجيد استعمالها في الواقع. ومن بين هذه النصوص أهمية النص البلاغي الإنشائي الذي سيكون محور النقاش ولكن بطريقة حداثية. وهذا يمنحنا فرصة عن: "تعليمية النص الإنشائي في الدرس اللغوي الحديث- أوستن أنموذجا -". ومحاولة الكشف عن:المشاكل التي تعترض طرفي العملية التعليمية أثناء تدريس النصوص اللغوية بصفة عامة  والبلاغية بصفة خاصة. أهم الطرائق المعتمدة في تدريس النصوص الإنشائية في الدرس اللغوي الحديث. النقائص التي تعاني منها طرائق التعليم. الحلول الممكنة للتخلص من هذه النقائص . Arabic language students from the problems suffered during received linguistic and literary texts; these problems appear inability actual language enhanced performance statistics. if mastered the texts of audio forms. morphological. syntactic. semantic and rhetorical it is not fluent in their use. in fact. among these texts importance rhetorical text construction. which will be the focus of discussion but modernist way. and this gives us an opportunity for: "educational construction text in the lesson linguistic  modern Austin model -". and try to detect: the problems facing both ends of the educational process during the teaching of the language texts in general and rhetorical particular. the most important methods certified in teaching texts in the construction of modern linguistic lesson. shortcomings experienced by the teaching methods. possible solutions to get rid of these shortcomings.